Latent periodic process inference from single-cell RNA-seq data - Shaoheng Liang (Nature Portfolio, 2020)
Traditional methods for determining cell type composition lack scalability, while single-cell technologies remain costly and noisy compared to bulk RNA-seq. Here, the authors present a highly efficient tool to measure cellular heterogeneity in bulk expression through robust integration of single-cell information.